Akcja Wyborcza Solidarność i Ruch Społeczny AWS w Rzeszowie - Szczepański, Dominik (Polityka i Społeczeństwo, 2021)
The purpose of the article is the presentation of the origins of the 1996 Solidarity Electoral Campaign, an electoral union composed of right-wing and centre-right parties. On the basis of this, the cornerstone of the political party AWS Social Movement was created. The conditions which led to the creation of the aforementioned subject in Rzeszow are subject to analysis, and the participation of AWS and AWS SM in parliamentary, local and presidential elections in the region is characterised. Issues which have a destructive impact on AWS and caused its dissolution are also discussed.